PURPOSE LEGISLATION STATUS (PSEUDOWETGEVING) AGAINST LEGAL REGULATIONS (ACCORDING TO LAW NUMBER 12 OF 2011 JO. LAW NUMBER 15 OF 2019 REGARDING THE ESTABLISHMENT OF LEGISLATION REGULATIONS) - Grace Sharon; Bintang Aulia Hutama; Levina Yustitianingtyas; Anang Dony Irawan (JHR (Jurnal Hukum Replik), 2023)
Pseudo-legislation (pseudovetgeving) in the Dutch Legal Dictionary is defined as “regelstelling door een bettokken bestuursorgaan zonder dat dit op grond van een uitdrukkelijke wettelijke bepaling die bevoegdheid bezit”. Which can be understood as a regulation made by the competent Administrative Body but the policy does not have the power based on explicit statutory provisions. In writing this article, there are three main ideas related to the background of the problems raised, namely the use of the legal system by the Indonesian state which is more inclined to the common law system or civil law system, the ordering of laws and regulations in Indonesia, and the position of pseudo legislation (pseudowetgeving) or policy regulations (beleidsregels) against existing laws and regulations in Indonesia. To provide comprehensive results, in writing articles used research methods that are normative juridical. The conclusions obtained in this study are that Indonesia is a state of law with a civil law system character that makes so many legal products issued by the executive body, including pseudo legislation. However, this is not explicitly regulated in Law Number 12 of 2011 Jo. Law Number 15 of 2019 concerning the Establishment of Legislation, but it is implied in the regulation of the National Archives of the Republic of Indonesia Number 5 of 2021 concerning General Guidelines for the Administration of Service Manuscripts, specifically in the section "regulation official documents and determination official documents". The conclusions obtained in this study are that Indonesia is a state of law with a civil law system character that makes so many legal products issued by the executive body, including pseudo legislation. However, this is not explicitly regulated in Law No. 12 of 2011 Jo. Law Number 15 of 2019 concerning the Establishment of Legislation, but it is implied in the regulation of the National Archives of the Republic of Indonesia Number 5 of 2021 concerning General Guidelines for the Administration of Service Manuscripts, specifically in the section "regulation official documents and determination official documents". The conclusions obtained in this study are that Indonesia is a state of law with a civil law system character that makes so many legal products issued by the executive body, including pseudo legislation. However, this is not explicitly regulated in Law Number 12 of 2011 Jo. Law Number 15 of 2019 concerning the Establishment of Legislation, but it is implied in the regulation of the National Archives of the Republic of Indonesia Number 5 of 2021 concerning General Guidelines for the Administration of Service Manuscripts, specifically in the section "regulation official documents and determination official documents".Keywords: Pseudo-Legislation (Pseudowetgeving); Hierarchy Of Laws And Regulations; Civil Law System.